2023
DOI: 10.1007/s10528-022-10318-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Genetic Diversity of Philippine Native Pigs (Sus scrofa) as Revealed by Mitochondrial DNA Analysis

Abstract: Philippine native pigs (PhNP) are small black pigs domesticated in rural communities in the Philippines. They are valued locally for their various sociocultural roles. Recently, considerable literature has accumulated in the field of native pig production and marketing. However, there is limited research on the genetic diversity of PhNP. No previous study has investigated the evolutionary relatedness among native pigs from various islands and provinces in Luzon and the Visayas, Philippines. In addition, a much… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 42 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…These multiple ancestries suggest high genetic variation among PhNPs on different islands. Furthermore, it revealed that the Cordillera Clade (which includes the Benguet [B] population) has ancestry distant from the general Asian clade (Banayo et al., 2023 ; Basilio Jr. et al., 2022 ), similar to the findings in the related Lanyu pig of Taiwan (Li et al., 2017 ; Wu et al., 2007 ). Moreover, PhNP interbreeds with endemic wild pigs of the Philippines, such as Sus philippensis , S. cebifrons , S. ahoenobarbus , S. olivieri , and S .…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…These multiple ancestries suggest high genetic variation among PhNPs on different islands. Furthermore, it revealed that the Cordillera Clade (which includes the Benguet [B] population) has ancestry distant from the general Asian clade (Banayo et al., 2023 ; Basilio Jr. et al., 2022 ), similar to the findings in the related Lanyu pig of Taiwan (Li et al., 2017 ; Wu et al., 2007 ). Moreover, PhNP interbreeds with endemic wild pigs of the Philippines, such as Sus philippensis , S. cebifrons , S. ahoenobarbus , S. olivieri , and S .…”
Section: Introductionmentioning
confidence: 60%
“…The initial ancestral polymorphisms between the D2 and D7 clades could explain the two initial clusters (k = 2) differentiating the NL and SLV regions, respectively (Figure 4). We previously hypothesized that the pigs of the D7 clade originated from the D2 clade via a genetic bottleneck event upon dispersal to Southeast Asia (Banayo, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent two studies (Banayo et al, 2023; Layos et al, 2022) reported the presence of a high frequency of MTSEA haplogroups (Layos et al, 2022, renamed MTSEA as D7) in native pigs in the Philippines, especially middle islands (South Luzon, Cebu, etc. ), as well as our result of the southern regions of Vietnam.…”
Section: Discussionmentioning
confidence: 99%